A New Perspective on Quality Evaluation for Control Systems with Stochastic Timing - Gaukler, Maximilian; Michalka, Andreas; Ulbrich, Peter; Klaus, Tobias (Proceedings of the 21st International Conference on Hybrid Systems: Computation and Control (HSCC '18), 2018)
As control applications are particularly sensitive to timing variations, the Quality of Control (QoC) is degraded by varying execution conditions of the underlying real-time system. In particular, transitions between different execution or environmental conditions pose a significant issue as they may impact the QoC unexpectedly. So far, the QoC is usually evaluated either in a stationary, time-invariant way, which cannot analyse said transitions, or by simulation, which becomes inefficient when confronted with random influencing factors. In this paper, we propose a new perspective on QoC evaluation for modern, adaptive real-time systems with varying timing conditions. For this, we present a time-variant stochastic assessment approach that incorporates the effects mentioned before. Our results demonstrate that adaptive scheduling and runtime behavior considerably impacts the QoC. At the same time, the proposed scheme significantly outperforms a traditional simulatio
Keywords: Quality of Control; Jitter; Real-time Systems; Automatic Control; Embedded systems; cyber-physical systems; Real-time systems; real-time; scheduling

Boosting Job-Level Migration by Static Analysis - Klaus, Tobias; Ulbrich, Peter; Raffeck, Phillip; Frank, Benjamin; Wernet, Lisa; Ritter von Onciul, Maxim; Schröder-Preikschat, Wolfgang (Proceedings of the 15th Workshop on Operating Systems Platforms for Embedded Real-Time Applications (OSPERT '19), 2019)

Closing the loop: Towards control-aware design of adaptive real-time systems - Klaus, Tobias; Franzmann, Florian Peter; Gaukler, Maximilian; Michalka, Andreas; Ulbrich, Peter (2016 IEEE Real-Time Systems Symposium, RTSS 2016, 2016)

Constrained Data-Age with Job-Level Dependencies: How to Reconcile Tight Bounds and Overheads - Klaus, Tobias; Becker, Matthias; Schröder-Preikschat, Wolfgang; Ulbrich, Peter (Proceedings of the 27th Real-Time and Embedded Technology and Applications Symposium (RTAS '21), 2021)

Data Propagation Delay Constraints in Multi-Rate Systems - Deadlines vs. Job-Level Dependencies - Klaus, Tobias; Franzmann, Florian Peter; Becker, Matthias; Ulbrich, Peter (Proceedings of the 26th International Conference on Real-Time Networks and Systems, 2018)

From Intent to Effect: Tool-based Generation of Time-Triggered Real-Time Systems on Multi-Core Processors - Franzmann, Florian Peter; Klaus, Tobias; Ulbrich, Peter; Deinhardt, Patrick; Steffes, Benjamin; Scheler, Fabian; Schröder-Preikschat, Wolfgang (Proceedings of the 19th IEEE Symposium on Real-Time Computing (ISORC 2016), 2016)
UnivIS-Import:2016-06-01:Pub.2016.tech.IMMD.IMMD4.fromin
Keywords: RTSC; AORTA; Multi-Core; Real-Time Systems

Poster Abstract: "Closing the Loop: Towards Control-aware Design of Adaptive Real-Time Systems" - Klaus, Tobias; Franzmann, Florian Peter; Gaukler, Maximilian; Michalka, Andreas; Ulbrich, Peter (Proceedings of the 37th Real-Time Systems Symposium (RTSS '16), 2016)

React in Time: Ereignisbasierter Entwurf zeitgesteuerter verteilter Systeme - Scheler, Fabian; Klaus, Tobias; Franzmann, Florian Peter; Ulbrich, Peter; Schröder-Preikschat, Wolfgang (Betriebsysteme und Echtzeit, 2015)
UnivIS-Import:2016-06-01:Pub.2015.tech.IMMD.IMMD4.reacti

Taking Control: Modular and Adaptive Robotics Process Control Systems - Ulbrich, Peter; Franzmann, Florian Peter; Harkort, Christian; Hoffmann, Martin; Klaus, Tobias; Rebhan, Anja; Schröder-Preikschat, Wolfgang (Proceedings of the 10th IEEE International Symposium on Robotic and Sensors Environments, 2012)
Robotics systems usually comprise sophisticated sensor and actuator systems with no less complex control applications. These systems are subject to frequent modifications and extensions and have to adapt to their environment. While automation systems are tailored to particular production processes, autonomous vehicles must adaptively switch their sensors and controllers depending on environmental conditions. However, when designing and implementing the process control system, traditional control theory focuses on the control problem at hand without having this variability in mind. Thus, the resulting models and implementation artefacts are monolithic, additionally complicating the real-time system design. In this paper, we present a modularisation approach for the design of robotics process control systems, which not only aims for variability at design-time but also for adaptivity at run-time. Our approach is based on a layered control architecture, which includes an explicit interface between the two domains involved: control engineering and computer science. Our architecture provides separation of concerns in terms of independent building blocks and data flows. For example, the replacement of a sensor no longer involves the tedious modification of downstream filters and controllers. Likewise, the error-prone mapping of high-level application behaviour to the process control system can be omitted. We validated our approach by the example of an autonomous vehicle use case. Our experimental results demonstrate ease of use and the capability to maintain quality of control on par with the original monolithic design. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.IMMD4.taking
Keywords: Architecture; Software Design; Operating Systems; Robotics and Automation; Sensor Systems; Control Engineering; Measurement System Data Handling; AORTA; ARES

Usable RTOS-APIs? - Klaus, Tobias; Franzmann, Florian Peter; Engelhard, Tobias; Scheler, Fabian; Schröder-Preikschat, Wolfgang (Proceedings of the 10th Annual Workshop on Operating Systems Platforms for Embedded Real-Time Applications, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD4.usable_0
Keywords: AORTA; RTSC